Aplikasi Layanan Informasi Dengan Metode Design Thinking Pada Barbertopia Kabupaten Nabire - Yuliawan, Kristia; Herba, Mei (STIKOM Tunas Bangsa Pematangsiantar, 2024)
Nabire Regency in Central Papua Province of Indonesia, is experiencing rapid development in the barbershop industry, reflecting economic growth and local cultural shifts. However, the industry faces challenges such as a lack of access to information and integrated services for consumers. This phenomenon encourages the application of a design-thinking approach to the development of effective barbershop information service applications. This research was designed using the design-thinking method, which includes five stages: empathy, definition, ideation, prototype, and trial. In the empathy stage, observations and interviews were conducted with Barbertopia customers in the Nabire Regency to understand their needs and problems. The results of this stage demonstrate the need for better access to information and more efficient queue management. The definition stage identifies the main problems, namely customer accumulation and information limitations. At the ideation stage, various solutions have been developed, including the creation of a mobile application that provides complete information about services, prices, and promos, as well as online booking features. The prototype of the application was then designed using Figma and tested using black-box testing techniques. The test results show that the application can meet the needs of users. The implementation of this application is expected to improve service efficiency, reduce waiting time, and increase customer satisfaction. The design-thinking approach has proven effective in designing user-oriented solutions, enabling Barbertopia Nabire Regency to improve the quality of its services and meet the expectations of modern customers in Nabire Regency.